The Question of Communist Violence and the Birth of Chinese Public Theology - Li, Quan (Studies in Christian ethics, 2022)
This article is a critique of Chinese public theologians with a particular focus on their Christological notions as ambivalent responses to Communist violence, a specific form of extreme violence in postcolonial China. The critique is historical as well as theological. As a historical inquiry, the problem of guerrilla warfare as a constant form of Communist violence is discussed, exploring its historical roots and philosophical manifestations. As a theological critique, it is demonstrated how this issue penetrates mainstream theo-political readings of Christ in the formation of Chinese public theology. The article thus seeks to contribute to the moral reflections of the Chinese church and the critical response to a unique form of postcolonial violence for Christian ethics.